Systematic investigation of the deformation mechanisms of a γ-TiAl single crystal. Issue 1 (December 2018) - Jeong, Byungkwan; Kim, Jaemin; Lee, Taegu; Kim, Seong-Woong; Ryu, Seunghwa
Abstract We propose a theoretical framework to predict the deformation mechanism of the γ-TiAl single crystal without lattice defects by combining the generalized stacking fault energy and the Schmid factor. Our theory is validated against an excellent testbed, the single crystal nanowire, by correctly predicting four major deformation mechanisms, namely, ordinary slip, super slip, twinning, and mixed slip/fracture observed during the tensile and compressive tests along 10 different orientations using molecular dynamics simulations. Interestingly, although lattice defects are not taken into account, the theoretical predictions match well with existing experiments on bulk specimen with only a few exceptions; the exceptions are discussed based on the size-dependent deformation mechanism in the presence of preexisting dislocation sources. We expect that the method in this paper can be generalized to study various ductile intermetallic crystals where conventional Schmid law does not hold well.